Analysis of Patch Test Results in both Paediatric and Adult Population with Suspected Allergic Contact Dermatitis and its Utility in Clinical Practice - Goyal, Pallavi (Advanced Concepts in Medicine and Medical Research Vol. 9, 2023)
The objective of the study was to find out patch test positivity rate in the specific region in patients with suspected allergic contact dermatitis (ACD) so that proper management of the patients can be done. Contact dermatitis is an inflammatory condition of the skin after exposure to any exogenous substance. It can be classified as irritant contact dermatitis (ICD) and allergic contact dermatitis (ACD). For evaluating the patch test positivity rate, a cross-sectional study was arranged in Mahatma Gandhi Hospital. This was done over a period of 3 months duration from March-May 2016. The number of participation was 68 who were suspected of contact dermatitis. All the patients were patch tested using the Indian Standard Series consisting of twenty common contact allergens which is approved by Contact and Occupational Dermatoses Forum of India (CODFI). The most common allergen found to be positive in both males and females was Parthenium followed by fragrance mix. Patch testing should be kept in mind when dealing with cases of suspected ACD, anogenital dermatitis, delayed hypersensitivity type cutaneous adverse drug reactions and specific site chronic dermatitis.